An Investigation into the Methods of Teaching Creative English Writing - Anastasiia Riabokrys; Olga Mishchenkob (Centre for Behaviour and Wellness Advocacy, 2016)
The article is devoted to the actual problem of teaching creative writing at the English lessons. The value of writing in the process of teaching English language is revealed. The principles and peculiarities of evaluation of creative writing are analyzed. The strategy of choosing methods in teaching creative writing is identified. The benefits of creative writing for learner and teachers are considered.